Green Star is not a physical activity star. Issue 1 (7th February 2017) - Creagh, Robyn; McGann, Sarah; Tye, Marian; Jancey, Jonine; Babb, Courtney
Abstract : Purpose: The purpose of this paper is to report on research investigating the relationship between physical activity and workplace design. In particular, the paper explores the social–ecological context of a new workplace building. This paper seeks to understand why better physical activity outcomes for the staff were not observed in the new building despite influence from a staff wellness committee during design; achieving success against existing best-practice indicators; and staff reporting increased feelings of wellness, energy and satisfaction with the new building. Design/methodology/approach: Three design aspects are taken as a focus from within an opportunistic pre-/post-physical activity study of an organisation as they move from a building they occupied for 30 years into a new purpose-designed building. This study was conducted through mixed methods, incorporating ethnographic, architectural and quantitative means. Findings: The social, spatial and personal context is important for understanding participant workplace-based physical activity. Despite the health and well-being goals and 5 Star Green Star outcomes of the new building, participants were sedentary for a substantive part of their workday in both buildings. Practical implications: A well-designed environment can support staff feeling healthier, but the 5 Star Green Star rating does not implicitly ensure a healthier, activity-promoting environment. Facilities managers and designers can act to provide physically active paths as the most straightforward circulation option in workplaces. Originality/value: The originality of this study lies in the opportunity to conduct a pre-/post-study of physical activity where the organisation, workforce and type of work are constant and where the variable is the building design, spatial configuration and location. The methods used in this study draw from both health promotion and architectural research practices.